Penerapan Model Guided Inquiry Terintegrasi STEM Untuk Meningkatkan Keterampilan Proses Sains Peserta Didik SMP Pada Materi Sistem Pernapasan Manusia - Alvyn Karina Lestari; Any Fitriani; Kusnadi (Postgraduate, University of Mataram, 2023)
This study was conducted with the aim of knowing the improvement of science process skills of students whose learning process uses a STEM-integrated guided inquiry learning model on human respiratory system material. The research method used was quasi experimental. The population in this study were all VIII science classes of State Junior High School totaling 175 students. The samples used were two classes taken with cluster random sampling technique. The normality value in the experimental class is 0.424 > 0.05 which is in the normal category, while the control class normality value is 0.120 > 0.05 which is in the normal category, The average N-Gain value in the experimental class is 0.60 and the average N-Gain value in the control class is 0.52, both N-Gain values are included in the medium category, the results of the independent t test 0.003 < 0.05 (Î±-0.05) which means that there is a significant difference between the science process skills of students in the experimental class and the control class. Based on the results of this study after applying the STEM-integrated guided inquiry model there is an increase in the science process skills of students in the experimental class on the human respiratory system.